Grammar form and function - Brouka, Milada (McGraw-Hill ESL/ELT, 2005)
Provides a visual context within the grammar charts for learning and retaining vocabulary and grammar. This title integrates study of new structures (form) with information on how to use them and what they mean (function). Its comprehensive grammar coverage ensures thorough and effective presentation of different basic structures